Soft skills for sustainable employment of business graduates of Bangladesh. Issue 3 (4th January 2019) - Nusrat, Mansura; Sultana, Nafia
Abstract : Purpose: The purpose of this paper is to examine whether soft skill requirements found in employer job postings (advertisements) within different roles of business are similar to the soft skills practically needed in the workplace and the perception of faculties at schools of business in Bangladesh. Design/methodology/approach: A two-phased study was administered. Phase 1 involved reviewing the latest relevant literature and hundreds of job advertisements; and in phase 2, questionnaires were administered to elicit responses from executives and faculty members from different universities in Bangladesh. Judgment sampling and the snowball technique were used to develop the sample of 84 respondents with a response rate of 56 percent. In total, 15 soft skills were used to develop the instrument. Descriptive statistics and a Kruskal–Wallis test were performed to analyze the collected data, where factors that retained α at or below 0.05, a family-wise Bonferroni adjustment (Mann–Whitney U test) was applied. Findings: All the mentioned soft skills are found to be desirable by the recruiters and faculties also agreed with them. However, there exist disparities on the perceived importance of four soft skills among faculties and recruiters, and a gap was found between the business curriculum and industry expectations from fresh-out business graduates. Originality/value: This study could be a basis for future studies and would help business education institutions guide their students to master the skills, and to develop and prepare them for real life battle in the job market. Moreover, the study indicates the gap between executives' expectations from the graduates and the institutional teaching provided by higher education institutions (for business majors), which would help practitioners reform their business curriculum to better ensure employability for their business graduates. Moreover, the study opens an avenue for further research in this field for implementing training programs for attaining the most desired soft skills among higher education institutions.